Structural basis of iron piracy by human gut Bacteroides - Augustinas Silale; Yung Li Soo; Hannah Mark; Rachel N. Motz; Arnaud Basle; Elizabeth M. Nolan; Bert van den Berg (Proceedings of the National Academy of Sciences, 2026)
Iron is an essential element that can be growth-limiting in microbial communities, particularly those present within host organisms. To acquire iron, many bacteria secrete siderophores, secondary metabolites that chelate ferric iron. These iron chelates can be transported back into the cell via TonB-dependent transporters in the outer membrane, followed by intracellular liberation of the iron. Pathogenic Escherichia coli and Salmonella produce siderophores during gut infection. In response to iron starvation, the human gut symbiont Bacteroides thetaiotaomicron upregulates an iron piracy system, XusABC, which steals iron-bound siderophores from the invading pathogens. Here, we investigated the molecular details of xenosiderophore uptake across the outer membrane by the XusAB complex. Our crystal and cryogenic electron microscopy structures explain how the XusB lipoprotein recognizes iron-bound xenosiderophores and passes them on to the XusA TonB-dependent transporter. Moreover, we show that Xus homologues can transport a variety of siderophores with different iron-chelating functional groups.